Penilaian Pendidikan Karakter dalam Pembelajaran Bahasa Indonesia di SMPN 3 Suppa Kabupaten Pinrang - Iqbal, Muh. Iqbal Asdiawan; Sultan, Sultan; Saleh, Muhammad Saleh (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to identify the form of character education assessment applied in Indonesian language learning and the obstacles faced by teachers in the assessment process. The research method used is qualitative with a descriptive approach. Data were collected through interviews, observations, and documentation. The results of the study indicate that character education assessment at SMPN 3 Suppa is carried out through various methods, including observation, self-assessment, and peer assessment. However, there are several obstacles faced, such as lack of teacher understanding, the large number of students in one class, and time constraints that make it difficult for teachers to provide accurate and in-depth assessments of each student's character. This study emphasizes the importance of managing the number of students in the class and the need for appropriate strategies in character assessment, such as dividing into small groups and using more efficient assessment methods.